Clinicopathologic and molecular profiles of Duchenne and Becker muscular dystrophy - Ery Kus Dwianingsih; Meydita Fuzia Putri Insani; Linda Pratiwi; Irianiwati Widodo; Rusdy Ghazali Malueka (Indonesian Pediatric Society, 2019)
Background Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are allelic X-linked recessive diseases caused by mutations in the dystrophin (DMD) gene. To our knowledge, molecular analysis to differentiate between DMD and BMD has never been performed in Indonesia. Objective To elaborate the clinicopathologic and molecular profiles of DMD/BMD patients in Yogyakarta, Indonesia. Methods Eighteen muscle biopsy specimens of patients clinically suspected to have DMD/BMD were collected. Possible associations of clinical manifestations, histopathological grading, and immunohistochemistry (IHC) results were analyzed. Polymerase chain reaction (PCR) was performed to identify mutations in exon 52. Results. Positive Gower’s sign and high serum creatine kinase (CK) were observed in most patients. The IHC of dystrophin in two female patients suggested that they were manifesting carriers. Of the 16 male patients, 12 showed negative IHC staining, indicating DMD, while 4 patients demonstrated weak expression of dystrophin, indicating BMD. There was a significant association between high CK level and IHC results (P=0.005), indicating higher CK level in DMD patients. Histopathological grading of muscle biopsy was significantly associated with diagnosis of DMD/BMD using IHC (P=0.01), showing more severe tissue damage in DMD patients. None of the subjects had the single exon 52 deletion. Conclusion This is the first report of a clinicopathologic and molecular profile of DMD/BMD in an Indonesian population. Serum CK level and histopathological grading of muscle biopsy are useful in distinguishing DMD from BMD in settings where an IHC assay is not available.